2018
DOI: 10.3904/kjim.2018.031
|View full text |Cite
|
Sign up to set email alerts
|

Middle East respiratory syndrome: what we learned from the 2015 outbreak in the Republic of Korea

Abstract: Middle East Respiratory Syndrome coronavirus (MERS-CoV) was first isolated from a patient with severe pneumonia in 2012. The 2015 Korea outbreak of MERSCoV involved 186 cases, including 38 fatalities. A total of 83% of transmission events were due to five superspreaders, and 44% of the 186 MERS cases were the patients who had been exposed in nosocomial transmission at 16 hospitals. The epidemic lasted for 2 months and the government quarantined 16,993 individuals for 14 days to control the outbreak. This outbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
174
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(182 citation statements)
references
References 87 publications
4
174
1
3
Order By: Relevance
“…Several studies of MERS-CoV viral load measurements show that upper respiratory tract specimens have lower viral loads than lower respiratory specimens. 11,12,79,80 MERS-CoV RNA has been detected in blood, urine, and stool-but at much lower viral loads than in the respiratory tract. 81,82 Clinical specimens must be collected by trained staff using appropriate personal protective equipmenteg, when taking nasopharyngeal and oropharyngeal specimens, Dacron or rayon swabs specifically designed for collecting specimens for virology must be used.…”
Section: Clinical Specimen Types For Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies of MERS-CoV viral load measurements show that upper respiratory tract specimens have lower viral loads than lower respiratory specimens. 11,12,79,80 MERS-CoV RNA has been detected in blood, urine, and stool-but at much lower viral loads than in the respiratory tract. 81,82 Clinical specimens must be collected by trained staff using appropriate personal protective equipmenteg, when taking nasopharyngeal and oropharyngeal specimens, Dacron or rayon swabs specifically designed for collecting specimens for virology must be used.…”
Section: Clinical Specimen Types For Diagnosismentioning
confidence: 99%
“…Several studies have reported disease severity and mortality risk factor data from patients in the Middle East and South Korea. 11,12,21,[114][115][116][117] Ahmed and colleagues collected the daily information on MERS-CoV cases posted online by the Saudi Arabian Ministry of Health between Dec 2, 2014, and Nov 12, 2016, and reviewed 660 laboratory-confirmed cases of MERS. 114 They showed mortality at day 3 (13·8%), day 30 (28·3%), and overall (29·8%).…”
Section: Management Outcomes and Mortality Ratesmentioning
confidence: 99%
See 3 more Smart Citations